Respiratory control in humans after 8 h of lowered arterial PO2, hemodilution, or carboxyhemoglobinemia. - Ren, X; Dorrington, K; Robbins, P (2001)
In humans exposed to 8 h of isocapnic hypoxia, there is a progressive increase in ventilation that is associated with an increase in the ventilatory sensitivity to acute hypoxia. To determine the relative roles of lowered arterial PO2 and oxygen content in generating these changes, the acute hypoxic ventilatory response was determined in 11 subjects after four 8-h exposures: 1) protocol IH (isocapnic hypoxia), in which end-tidal PO2 was held at 55 Torr and end-tidal PCO2 was maintained at the preexposure value; 2) protocol PB (phlebotomy), in which 500 ml of venous blood were withdrawn; 3) protocol CO, in which carboxyhemoglobin was maintained at 10% by controlled carbon monoxide inhalation; and 4) protocol C as a control. Both hypoxic sensitivity and ventilation in the absence of hypoxia increased significantly after protocol IH (P < 0.001 and P < 0.005, respectively, ANOVA) but not after the other three protocols. This indicates that it is the reduction in arterial PO2 that is primarily important in generating the increase in the acute hypoxic ventilatory response in prolonged hypoxia. The associated reduction in arterial oxygen content is unlikely to play an important role.